Expanding Role of the Jumonji C Domain as an RNA Hydroxylase - Noma, Akiko (American Society for Biochemistry and Molecular Biology, 2010)
JmjC (Jumonji C) domain-containing proteins are known to be an extensive family of Fe(II)/2-oxoglutarate-dependent oxygenases involved in epigenetic regulation of gene expression by catalyzing oxidative demethylation of methylated histones. We report here that a human JmjC protein named Tyw5p (TYW5) unexpectedly acts in the biosynthesis of a hypermodified nucleoside, hydroxywybutosine, in tRNA(Phe) by catalyzing hydroxylation. The finding provides an insight into the expanding role of JmjC protein as an RNA hydroxylase.